The effect of using different oils and paper towel in vegetable oil absorption of fried recipes. Issue 4 (4th July 2019) - de Lima, Kellen Cristina Marques; Barros, Helena Dias de Freitas; Passos, Thais Souza; Maciel, Bruna Leal Lima
ABSTRACT: This work determined the effect of using different vegetable oils (soybean, corn, sunflower or canola) and paper towel in oil absorption of nine fried recipes. The paper towel significantly reduced oil absorption in chicken breast, shrimp with garlic, cioba steak, French fries and cheese samosa. Preparations protein-rich absorbed less soybean and corn oils, while starch-rich ones absorbed less of the sunflower and canola oils, with the exception of French toast. Results indicated that food composition of the tested recipes was an important factor influencing oil absorption, as well as the types of oil tested and the use of paper towel.